2003
DOI: 10.1046/j.1471-0528.2003.01507.x
|View full text |Cite
|
Sign up to set email alerts
|

Term breech presentation in The Netherlands from 1995 to 1999: mortality and morbidity in relation to the mode of delivery of 33,824 infants

Abstract: Objective To analyse neonatal mortality and morbidity in term infants born in breech presentation in relation to the mode of delivery (planned caesarean section, emergency caesarean section or vaginal delivery) and to compare these findings with those of the Term Breech Trial Collaborative Group [Hannah et al. Lancet 2000; October]. Design Retrospective observational study. Setting The Netherlands. Population Infants (n ¼ 33,824) born at term in breech presentation in the Netherlands between 1995 and 1999. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
3
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 17 publications
3
46
3
3
Order By: Relevance
“…Studies 2,3,4,29,30,31 have reported better neonatal morbidity in the form of low apgar scores, neonatal intensive care admissions, birth trauma in breech born by elective caesarean section and recommend caesarean section for breech. On the contrary, several authors have reported good neonatal outcomes win patients undergoing vaginal breech birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies 2,3,4,29,30,31 have reported better neonatal morbidity in the form of low apgar scores, neonatal intensive care admissions, birth trauma in breech born by elective caesarean section and recommend caesarean section for breech. On the contrary, several authors have reported good neonatal outcomes win patients undergoing vaginal breech birth.…”
Section: Discussionmentioning
confidence: 99%
“…The number of caesarean section increased worldwide reaching to 80% at some places. [2][3][4] Guidelines from U.K 5 and USA 6 endorsed the policy of caesarean section for all term breech patients. The global reaction to trial has been exceptional because obstetricians face a dilemma when it comes to breech delivery especially in primigravida.…”
Section: Introductionmentioning
confidence: 99%
“…They generally report considerably increased neonatal risks in the vaginal delivery group. 1,[14][15][16] The many patients included in such studies allow statistically significant comparisons but their results are difficult to interpret because of the questionable validity and sparseness of the antenatal and postnatal information. In the PRE-MODA study, data were collected to answer the question about the association between mode of delivery and serious neonatal morbidity or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…As described in the introduction chapter, different populations were found to have slightly near incidence of breech presentation, with some exceptions, like the Netherlands' population [2][3][4][5]. Probably, particular ethnic pelvic conformations could be responsible for different prevalence of fetal breech presentation at delivery.…”
Section: Ethnicitymentioning
confidence: 94%
“…The breech presentation is a quiet common occurrence in the obstetrical practice, accounting for about 3-5% of singleton fetuses at delivery [1][2][3][4], even if percentages as high as 8.2% have also been reported [5]. It represents a challenging vaginal delivery condition, for which a large number of obstetrical maneuver have been described during the past years (e.g.…”
Section: Introductionmentioning
confidence: 99%